Effects of Authoritative Guidance Availability and Audit Committee Effectiveness on Auditors' Judgments in an Auditor-Client Negotiation Context - Ng, Terence Bu-Peow; Tan, Hun-Tong (The Accounting Review, 2003)
In this paper, we present the results of an experiment that investigates the effects of two contextual features—the availability of authoritative guidance and the effectiveness of the client's audit committee—on auditors' perceived outcome of auditor-client negotiations concerning an audit adjustment that affects the client's ability to meet analysts' forecasts. Results show that auditors' perceived negotiation outcome is jointly influenced by authoritative guidance availability and audit committee effectiveness. Specifically, authoritative guidance availability has a greater effect on auditors' perceived negotiation outcome in the absence of an effective audit committee than in its presence. We also find that concessionary moves by the client increase auditors' propensity to concede to the client's preferred position.